Risk factors for in-hospital complications in patients with acute ischemic stroke: Retrospective cohort in a national reference hospital in Peru - Miguel A. Vences; Virgilio E. Failoc-Rojas; Diego Urrunaga-Pastor; Yamilée Hurtado-Roca (Heliyon, 2023)
Objective: To describe the clinical and demographic characteristics of patients with acute cerebral infarction treated at a national reference hospital in Peru and determine the risk factors for in-hospital complications. Methods: We conducted a retrospective cohort study including 192 patients with acute ischemic stroke in a national reference hospital in Peru from January to September 2021. Clinical, demographic and paraclinical information was recorded from medical records. We estimated risk ratios and 95% confidence intervals using regression models with Poisson family and robust variance for the bivariate and multivariate model, adjusting for age, sex and risk factors for stroke. Results: At least one in-hospital complication occurred in 32.3% of the patients. The most frequent complications were infectious in 22.4%, followed by 17.7% of neurological complications, with other complications, such as thromboembolism, immobility and miscellaneous, being much less frequent. Regression analysis showed that stroke severity (RR = 1.76; 95%CI:1.09–2.86) and albumin greater than 3.5 mg/dL (RR = 0.53; 95%CI: 0.36–0.79) were independent risk factors for the presence of in-hospital complications. Conclusions: A high rate of in-hospital complications were observed, among which infectious and neurological complications were the most frequent. Stroke severity was a risk factor and albumin greater than 3.5 mg/dL was a protective factor for the incidence of in-hospital complications. These results can serve as a starting point for establishing stroke care systems that consider differentiated flows for the prevention of in-hospital complications.